Changing patterns of social variation in stature in Poland - Bielicki, T; Szklarska, A; Koziel, S; Ulijaszek, S (Cambridge University Press, 2005)
Summary: The aim of this analysis was to examine the effects on stature in two nationally representative samples of Polish 19-year-old conscripts of maternal and paternal education level, and of degree of urbanization, before and after the economic transition of 1990. Data were from two national surveys of 19-year-old Polish conscripts: 27,236 in 1986 and 28,151 in 2001. In addition to taking height measurements, each subject was asked about the socioeconomic background of their families, including paternal and maternal eduction, and the name of the locality of residence. The net effect of each of these social factors on stature was determined using four-factor analysis of variance. The secular trend towards increased stature of Polish conscripts has slowed down from a rate of 2.1 cm per decade across the period 1965-1986 to 1.5 cm per decade between 1986 and 2001. In both cohorts, mean statures increase with increasing size of locality of residence, paternal education and maternal eduction. The effect of each of these three social factors on conscript height is highly significant in both cohorts. However, the effect of maternal eduction has increased substantially while that of size of locality of residence and paternal education diminished between 1986 and 2001. These results imply that the influence of parental education on child growth cannot be due solely to a relationship between education and income, but is also perhaps a reflection of household financial management which benefits child health and growth by better educated parents, regardless of level of income. In addition they suggest that, irrespective of whether there are one or two breadwinners in the family, it is the mother, more so thanthe father, who is principally responsible for the extent to which such management best favours child health and growth. The asymmetry between the importance of maternal as against paternal education for child growth, clearly seen in the 1986 cohort, became more accentuated in 2001, after the abrupt transition from a command to a free-market economy in the early 1990s.